Distribution of serotypes of human rotavirus in different populations. - Woods, P A (1992)
Serotyping is a useful tool to study the epidemiologic characteristics of rotaviruses in large populations and to assess the need for a vaccine to protect against all strains. By using an enzyme immunoassay with serotype-specific monoclonal antibodies to the four most common rotavirus serotypes, we analyzed 1,183 rotavirus-positive specimens from 16 stool collections in eight countries on four continents that were obtained from 1978 to 1989. Of the 926 strains (78%) that could be serotyped, 48% were serotype 1, 8% were serotype 2, 15% were serotype 3, and 7% were serotype 4. Twenty-two percent had insufficient numbers of double-shelled virus particles to react with the monoclonal antibody of the VP4 rotavirus protein and therefore could not be serotyped. Our results indicate that vaccines being developed must provide the greatest coverage against serotype 1 and that the serotype distribution cannot be predicted currently by the geographic area or prevalence in the preceding year.